MANAJEMEN LABA (EARNING MANAGEMENT) DALAM PERSPEKTIF ETIKA HEDONISME - Rama, Radian Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Earnings management occurs as a direct consequence of the efforts of managers or preparers of financial statements for management accounting information, especially earnings for the sake of personal interests or companies. That earnings management can not be interpreted as a negative action since it does not profit-oriented management of earnings manipulation. Positive accounting theory suggests that managers have an incentive or encouragement to be able to maximize their welfare. In this paper the behavior of managers in the conduct of earnings management will be reviewed from the standpoint of ethical hedonism. Used in the sense of ethical values and moral norms which become the handle for one person or a group to regulate behavior hedonism Ethics plays an important role of earnings management. Because hedonism starting from the assumption that human beings should live in such a way that it can be more happy. Efforts to gain reward management priorities, reward obtained by showing a stable performance from several periods. Earning management one way to show achievement. By looking at two perspectives of psychological hedonism and ethical hedonism, it can be drawn a conclusion that earning management is a reasonable action to meet the man himself hedonism.Keywords: Earnings Management, Positive Accounting Theory, EthicalÂ Â  Hedonism